Workplace Holistic Health & Wellness: Primary care program to address lifestyle disorders - Kumar, Santosh; Gupta , Kanchan; Joshi, Anubhuti (Indian Journal of Community Health, 2025)
The global upsurge in lifestyle diseases, which account for 74% of global fatalities, poses a critical threat. Life style diseases including cardiovascular diseases and diabetes, are increasingly burdening low and middle income countries. The aim of this article to address integration of primary healthcare with public health strategies, as advocated by the 1978 Alma-Ata Declaration. This approach emphasizes community participation and equitable access to care. Adopting a holistic wellness paradigm—encompassing physical, mental, and spiritual well-being—extends beyond the traditional definitions of health. This integration fosters sustainable, community-centred health systems capable of effectively managing the Life style disease crisis. The study proposes a workplace wellness model, emphasizing its positive impact on individual and organizational productivity. Implementation of this model through sensitization, need assessment, economic productivity in terms of sound health and wellness for organisation. Similar program through Youth upliftment and awareness: journey towards optimism, strength and harmony (YUWA JOSH) among university students aims to improve academic and social performances, creating a healthier youth community. A wellness program, as a primary care strategy, addresses lifestyle diseases by promoting awareness and preventing diseases before complications arise. This approach is crucial as it links early wellness habits to long-term productivity and health resilience.